Religious Inspirations for Social Rehabilitation and Educational Activities. Testimonies of Participants of the Teen Challenge Training Programs in Poland - Patalon, Mirosław (Paedagogia Christiana, 2023)
This article shows the conceptual similarities between the ecclesial and secular understanding of resilience and probation, the evangelical foundations and connections between these concepts and the pedagogical and social rehabilitation activities. This discussion provides the background for the history of the Teen Challenge movement and its contemporary activity in the world and in Poland. Particular attention is paid to the rehabilitation centre in Broczyna near Słupsk, Poland. Following this theoretical framework, excerpts from the testimonies of the centre’s therapeutic program participants are presented along with a phenomenographic map of the basic categories repeated in their statements. The specificity of the discussed therapy appears to lie in the belief in God and reliance on him in the process of recovery resulting from the assumptions of negative anthropology (human weakness).